MENAKAR KEDUDUKAN AL-MAL DALAM EKONOMI ISLAM - Syahputra, Rizki; Andhika, Muhammad Rezki (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
The Islamic economic system gives individuals freedom in economics. Encourage individuals to work and not deny individual ownership of the world's property. But on the other hand, Islam invites individuals to love and love their fellow Muslim brothers and include them for the gift of their wealth. The term HARTA, or al-mal in the Qur'an or Sunnah is not limited in the scope of a certain meaning, so the understanding of al-Mal is very broad and always evolving. The criteria of property according to fiqh experts consist of: first, it has an element of economic value. Second, the element of benefits or services obtained from an item. Islamic view of property can be described as follows: 1), The Absolute Owner of everything on the earth is ALLAH SWT. 2), the status of human property is as follows: a. property as a trust (deposit) from Allah SWT. Man is only a trustee because he is not able to hold things from nothing. b. Treasure as a living adornment that allows man to enjoy it well and not excess. 3), Ownership of property can be done through efforts ('deeds) or livelihoods (Ma'isyah) that are lawful and in accordance with the rules of God. 4) it is forbidden to seek property, try or work that forgets death, 5): it is forbidden to pursue illegal business.